Stratified medicine using invasive coronary function testing in angina: A cost-effectiveness analysis of the British Heart Foundation CorMicA trial. (15th August 2021) - Heggie, R.; Briggs, A.; Stanley, B.; Good, R.; Rocchiccioli, P.; McEntegart, M.; Watkins, S.; Eteiba, H.; Shaukat, A.; Lindsay, M.; Robertson, K.; Hood, S.; et al.
Abstract: Aim: Coronary angiography is indicated in many patients with known or suspected angina for the investigation of coronary artery disease (CAD). However, up to half of patients with symptoms of ischaemia have no obstructive coronary arteries (INOCA). This large subgroup includes patients with suspected microvascular angina (MVA) and/or vasospastic angina (VSA). Clinical guidelines relating to the management of patients with INOCA are limited. Uncertainty regarding the diagnosis of patients with INOCA presents a health economic challenge, both in terms of healthcare resource utilisation and of quality-of-life impact on patients. Methods: A cost-effectiveness analysis of the introduction of stratified medicine into the invasive management of INOCA, based on clinical and resource-use data obtained in the CorMicA trial, from a UK NHS perspective. The intervention included an invasive diagnostic procedure (IDP) of coronary vascular function during coronary angiography to define clinical endotypes to target with linked medical therapy. Outcomes of interest were mean total cost and QALY gain between treatment groups, and the incremental cost-effectiveness ratio. We undertook probabilistic sensitivity and scenario analyses. Results: The incremental cost per QALY gained at 12 months was £4500 (£2937, £33264). Compared with a willingness-to-pay (WTP) threshold of £20, 000 per QALY, the use of the IDP test is cost-effective. At this WTP threshold there is a 96% probability of the IDP being cost-effective, based on the uncertainty described by bootstrap analysis. Conclusions: The burden of INOCA, particularly in women, is known to be significant. These findings provided new evidence to inform this unmet clinical need. Graphical abstract: Unlabelled Image Highlights: Up to half of patients with signs and/or symptoms of ischaemia have no obstructive coronary arteries (INOCA). The burden of INOCA, particularly in women, is known to be significant. Adjunctive testing to tailor treatment based on patient endotype is associated with an increase in cost and quality of life. With an ICER of £4, 500, such a clinical strategy would be highly cost-effective in a UK setting. Adjunctive testing allows for stratification of this undifferentiated subpopulation and targeting of linked medical therapy.